Circulating biomarker panels for targeted therapy in brain tumors. (February 2015) - Tanase, Cristiana; Albulescu, Radu; Codrici, Elena; Popescu, Ionela Daniela; Mihai, Simona; Enciu, Ana Maria; Cruceru, Maria Linda; Popa, Adrian Claudiu; Neagu, Ana Iulia; Necula, Laura Georgiana; Mambet, Cristina; Neagu, Monica
ABSTRACT : An important goal of oncology is the development of cancer risk-identifier biomarkers that aid early detection and target therapy. High-throughput profiling represents a major concern for cancer research, including brain tumors. A promising approach for efficacious monitoring of disease progression and therapy could be circulating biomarker panels using molecular proteomic patterns. Tailoring treatment by targeting specific protein–protein interactions and signaling networks, microRNA and cancer stem cell signaling in accordance with tumor phenotype or patient clustering based on biomarker panels represents the future of personalized medicine for brain tumors. Gathering current data regarding biomarker candidates, we address the major challenges surrounding the biomarker field of this devastating tumor type, exploring potential perspectives for the development of more effective predictive biomarker panels.